Synthesis of spirofused carbohydrate-oxazoline based palladium(II) complexes. (26th June 2015) - Kraft, Jochen; Ziegler, Thomas
Abstract: Four carbohydrate-derived 2-pyridyl and 2-quinolinyl substituted spiro-oxazoline ligands were prepared from 3, 4, 5-tri-O-benzyl-1, 2-di-O-isopropylidene-β-d -fructose in four steps. Conversion of the latter compound with trimethylsilylazide followed by hydrogenation gave an anomeric mixture of 2-amino-3, 4, 5-tri-O-benzyl-2-deoxy-1-O-trimethylsilyl-d -fructopyranose. Amide coupling of the fructosylamines with picolinic acid and quinaldic acid, respectively afforded the corresponding anomeric amidofructosides, which were both separated and characterized by NMR spectroscopy and X-ray crystallography. Cyclization of alpha-amides was achieved by treatment of the corresponding mesylates with NaH while beta-amides were directly cyclisized with NCS and Ph3 P to give the corresponding 2-pyridyl (PyOx) and 2-quinolyl (QuinOx) substituted spiro-oxazoline ligands, respectively. The 2-pyridyl substituted spiro-oxazoline ligands PyOx formed stable complexes with Pd(II), which were fully characterized and their structure determined by X-ray crystallography, whereas the corresponding QuinOx ligands failed to form similar Pd complexes. Graphical abstract: Highlights: Four spirofused fructo -configurated PyOx and QuinOx ligands were prepared. Anomeric configuration of ligands and intermediates was assigned by NMR and X-ray. PyOx ligands formed stable complexes with Pd(II), which were fully characterized. Structure of Pd(II) complexes were proven by X-ray crystallography.